Developing life long learners through information literacy programmes: case study of Hospital Universiti Kebangsaan (HUKM) Library - Kadir, Maimunah; Mohd Saad, Mohd Sharif (Persatuan Pustakawan Malaysia, 2005)
Libraries today acknowledge the importance of life long learning among their users, in their work and in their everyday life. Many believe it can be achieved through information literacy skills. Information literate are those who have learnt how to learn and are prepared for life long learning. They can always find the information needed for any task or decision—making. Recognizing these needs, many libraries of institutions of higher learning including Hospital Universiti Kebangsaan (HUKM) Library, implement programmes to develop information competencies of their users.